2014
DOI: 10.1007/s00223-014-9892-1
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone (1-34) Modulates Odontoblast Proliferation and Apoptosis via PKA and PKC-Dependent Pathways

Abstract: Parathyroid hormone (PTH) plays a key role in the development and homeostasis of mineralized tissues such as bone and dentine. We have reported that PTH (1-34) administration can increase dentine formation in mice and that this hormone modulates in vitro mineralization of odontoblast-like cells. The purpose of the present study was to investigate whether PTH (1-34) participates in the proliferative and apoptotic signaling of odontoblast-like cells (MDPC23). MDPC23 cells were exposed to 50 ng/ml hPTH (1-34) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Prolonged PTH (1–34) exposure, for different durations, results in different degrees of PKC pathway stimulation [ 41 ]. Some studies have reported that PTH (1–34) exposure for 24 or 48 h results in the activation of the PKC pathway [ 42 ]. Therefore, PTH (1–34) activation, resulting in stimulation of either the PKC or PKA pathway, might be dependent on and influenced by PTH (1–34) treatment time, dose, absorption, and elimination or half-life.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged PTH (1–34) exposure, for different durations, results in different degrees of PKC pathway stimulation [ 41 ]. Some studies have reported that PTH (1–34) exposure for 24 or 48 h results in the activation of the PKC pathway [ 42 ]. Therefore, PTH (1–34) activation, resulting in stimulation of either the PKC or PKA pathway, might be dependent on and influenced by PTH (1–34) treatment time, dose, absorption, and elimination or half-life.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to evaluate the association between SNPs in the PTH gene and dental caries in Brazilian children. PTH influences tooth formation, since the odontogenesis-related cells differentiate until dentin and enamel synthesis (4,6,7). There is evidence that odontoblasts, cementoblasts and ameloblasts, specific cells of tooth formation, express the PTH receptor 1 (PTHR1) and are sensible to PTH serum levels (7,24).…”
Section: Discussionmentioning
confidence: 99%
“…PTH influences tooth formation, since the odontogenesis-related cells differentiate until dentin and enamel synthesis (4,6,7). There is evidence that odontoblasts, cementoblasts and ameloblasts, specific cells of tooth formation, express the PTH receptor 1 (PTHR1) and are sensible to PTH serum levels (7,24). Although the effects of PTH on cementoblasts and ameloblasts are not fully understood (24), in vitro studies (7) and studies evaluating PTH-knockout mice (6) indicate that PTH modulates the proliferative and apoptotic responses of odontoblasts, suggesting that modifications in PTH serum levels during odontogenesis can affect dentine and enamel quality and increase the risk and progression of dental caries (6,7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time-dependent action of PTH might be due to differences in the signal transduction systems, indicating a synchronized regulation of cAMP/PKA and PKC signaling after PTH stimulation [ 39 ]. While the PKA pathway acts in response to short exposure to PTH, the PKC pathway is mainly involved at longer times of exposure in an antagonist mode [ 40 , 41 ]. In our study, STRO-1(+) PDLSCs were treated under the intermittent administration of PTH, which might be mediated predominantly by cAMP/PKA pathway.…”
Section: Discussionmentioning
confidence: 99%